РЕАЛІЗАЦІЯ КРИМІНАЛЬНОГО ЗАКОНОДАВСТВА: ПОНЯТТЯ, ОЗНАКИ ТА МЕХАНІЗМ - Бабаніна, Вікторія (SUPREMANCE OF LAW, 2019)
This article is concerning on studying of criminal legislation realization definition; its features as well as some provisions on criminal legislation realization mechanism have been disclosed. It is acknowledged criminal legislation realization is a structural element of criminal law regulation and simultaneously its closing stage. Semantic meaning of criminal legislation realization mechanism has been given in three aspects as: certain system; certain method or means; assemblage of certain processes. It was proposed to contemplate criminal legislation realization mechanism in its broad and narrow meanings. An attention was paid to the fact that realization mechanism is a process on the one hand and a result on the other. A necessity to distinguish general (concerning realization of all criminal legislation), special (concerning realization of certain criminal legal norm or some such norms within one or several criminal legal institutes) and individual (concerning criminal legal norms realization in certain real-life situation) levels of criminal legislation realization mechanism has been argued.
Keywords: criminal legislation; criminal legislation realization; criminal legislation realization mechanism; criminal responsibility; criminal law regulation; criminal law norm; criminal law relations